STUDY ON TRUNK ASYMMETRY IN CHILDREN AGED 10-15 YEARS - Béla József BALLA; Iacob HANȚIU (Cluj University Press, 2016)
Background: A school screening for trunk asymmetries was performed in 2015, to assess children and teenage population the prevalence of these asymmetries. Objectives: To report the prevalence of trunk asymmetry in normal children and adolescents in Cluj-Napoca, by a cross-sectional study. Methods: The traditional Adam's forward bending test and scoliometer readings were used during the screening program to collect quantitative data. The angle of trunk rotation was measured to quantify the existing trunk asymmetry. A number of 373 subjects (199 male and 174 female) were screened, with a mean age of 13.0 ±1.48 (girls 12.73±1.51; boys 13.26±1.41). Results: The subjects were divided into two groups according to the severity of trunk asymmetry. In the first group, asymmetry was 1 to 6 degrees and in the second group was 7 or more degrees. The mean frequency of (severe) asymmetry of 7 or more degrees was 1.84% in boys and 7.28% in girls. The mean frequency of symmetric (angle of trunk rotation = 0 degrees) boys and girls was 70.5% and 66.7%, respectively. Conclusions: 47.7% of boys and 41.7% of girls were found to be absolutely symmetric in all regions of the spine. Girls are found to have a higher frequency of asymmetry than boys do. Right trunk asymmetry was more common than left. These findings are also supported by several studies from other European regions.  Studiul asimetriei trunchiului la copiii cu vârsta cuprinsă între 10-15 ani. Introducere: În 2015 a fost efectuat un screening școlar pentru depistarea asimetriei trunchiului, cu scopul de a raporta prevalența acestei asimetrii la copiilor de vârstă școlară. Obiective: Raportarea prevalenței asimetriilor trunchiului la copiii și adolescenții sănătoși la Cluj-Napoca, printr-un studiu transversal. Metode: În cadrul acestui program de depistare au fost folosite testul Adam's - testul înclinării spre înainte - și măsurarea scoliometrică pentru a colecta date cantitative. Unghiul de rotație a trunchiului a fost măsurat pentru a cuantifica distorsiunile torsului. Au fost incluși 373 de subiecți (199 băieți și 174 fete), vârsta medie a elevilor fiind 13,0 ±1,48 (fete 12,73±1,51; băieți 13,26±1,41). Rezultate: Subiecții au fost împărțiți în două grupuri în funcție de severitatea asimetriei trunchiului. În primul grup au fost clasați cei cu asimetrii între 1 și 6 grade, iar în al doilea cei cu asimetria de 7° sau de la 7° în sus. Frecvența asimetriilor severe (7°≤) este de 1,84% la băieți și de 7,28% la fete. Frecvența spatelui simetric (unghiul de rotație a trunchiului = 0°) la băieți este de 70,5% și respectiv de 66,7% la fete. Concluzii: Din această cercetare reiese că fetele sunt mai afectate de asimetriile spatelui decât băieții. Asimetria toracică dreaptă este mult mai des întâlnită, decât cea stângă. Aceste constatări sunt susținute și de alte studii făcute în regiunile Europei.  Cuvinte-cheie: asimetria trunchiului, screening școlar, scolioză, măsurare scoliometrică.